RADIOACTIVITY LEVELS OF LIMESTONE AND GYPSUM USED AS BUILDING RAW MATERIALS IN TURKEY AND ESTIMATION OF EXPOSURE DOSES - Turhan, Şeref (Radiation Protection Dosimetry (2010), pp. 1–6, 2010)
The natural radionuclide contents of limestone and gypsum samples used as building raw materials in Turkey were measured by means of gamma spectrometer system with HPGe detector. The measured activity concentrations of 226Ra, 232Th and 40K radionuclide were compared with the reported data from other countries. Radium equivalent activity and internal hazard index, absorbed gamma dose rate in indoor due to the external exposure and corresponding annual effective dose were determined to estimate the exposure risk arising due to the use of these raw materials. This study has shown that examined gypsum and limestone raw materials do not pose any excess radiological health problem and are safe for use in the construction of buildings.
Keywords: RADIOACTIVITY LEVELS, LIMESTONE AND GYPSUM, RAW MATERIALS